2013
DOI: 10.4236/mrc.2013.24017
|View full text |Cite
|
Sign up to set email alerts
|

N-Hexane Isomerization on Ni-Pt/Catalysts Supported on Mordenite

Abstract: The aim of this work was to evaluate the catalytic properties for n-hexane isomerization of bifunctional monometallic (Ni or Pt) and bimetallic catalysts (Pt-Ni), using HMOR zeolite as support. The method used for metal dispersion in the zeolite was competitive ion exchange using ammine complexes [Ni(NH 3) 6 ]Cl 2 and [Pt(NH 3) 4 ]Cl 2 as precursors. The catalysts were characterized by X-Ray diffraction, X-Ray energy dispersion spectroscopy, temperature-programmed reduction and transmission electron microscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Similarly, Nasser et al revealed that dealumination of MOR zeolite with 1 M nitric acid for 20 min of treatment gave only 20% catalytic conversion of n -hexane that is reduced to 17.3% after 240 min of treatment mainly due to pore blockage by reduction of mesopore channels or coke. Martins and his research group demonstrated that the 40Ni60Pt/H-MOR catalyst showed the maximum n -hexane conversion of about 24%, while 60Ni40Pt/H-MOR revealed 99% selectivity at 250 °C . It is concluded that a temperature of 300 °C is an optimum temperature to obtain about 90–94% isomerization selectivity with about 77% conversion of n -hexane by all Ba and Sr modified Pt-zeolites.…”
Section: Resultsmentioning
confidence: 97%
“…Similarly, Nasser et al revealed that dealumination of MOR zeolite with 1 M nitric acid for 20 min of treatment gave only 20% catalytic conversion of n -hexane that is reduced to 17.3% after 240 min of treatment mainly due to pore blockage by reduction of mesopore channels or coke. Martins and his research group demonstrated that the 40Ni60Pt/H-MOR catalyst showed the maximum n -hexane conversion of about 24%, while 60Ni40Pt/H-MOR revealed 99% selectivity at 250 °C . It is concluded that a temperature of 300 °C is an optimum temperature to obtain about 90–94% isomerization selectivity with about 77% conversion of n -hexane by all Ba and Sr modified Pt-zeolites.…”
Section: Resultsmentioning
confidence: 97%
“…According to the literature, [7][8][9] one of the most effective catalysts for the isomerization of linear hexane, an industrially important reaction used to increase the octane number of the pentane-hexane fraction of oil, is mordenite. The prospect of using natural zeolites of Transcarpathia with predominantly mordenite components for these purposes was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Bimetallic (Ni−Pt)/MOR and monometallic (Pt or Ni) catalysts and were evaluated in a fixed-bed reactor at 0.1 MPa, 250 °C, and H 2 /n-hexane molar ratio of 9. 45 The temperatureprogrammed reduction (TPR) profiles suggested that the presence of Pt contributed to the reduction of Ni 2+ cations in bimetallic catalysts. The bimetallic catalysts showed better activity for isomerization of n-hexane and improved stability upon increasing their Pt content.…”
Section: Isomerization Of C 5 −C 6 Alkanesmentioning
confidence: 99%